1989
DOI: 10.1203/00006450-198905000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Rheologic Properties of Neonatal and Adult Blood

Abstract: ABSTRACT. A number of studies have indicated that the emphasis on low shear rate viscosity and rouleaux-related pherheologic properties of neonatal blood are different from nomena. those of the adult. The frequent administration of blood components to the neonate during intensive care make it important that these differences be established and their MATERIALS AND METHODS causes understood. The purpose of this study was to make a detailed comparison of the rheologic properties of nee-Blood was obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“…This may be due to desialylation of RBC membrane glycoconjugates caused by cleavage of terminal SA residues, facilitating the antigen-antibody binding used. The possible influence of age could also be considered, as the healthy volunteers were younger than the septic patients, but RBC membrane glycophorin A content is not influenced by age (27). The present results contradict the current view described in senescence or hemolytic processes (11,28) that alterations in RBC deformability are due to membrane loss, but they are in agreement with the results of Nieuwland et al (29) in meningococcal sepsis, who found no difference in the glycophorin A plasma content in septic patients compared with healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to desialylation of RBC membrane glycoconjugates caused by cleavage of terminal SA residues, facilitating the antigen-antibody binding used. The possible influence of age could also be considered, as the healthy volunteers were younger than the septic patients, but RBC membrane glycophorin A content is not influenced by age (27). The present results contradict the current view described in senescence or hemolytic processes (11,28) that alterations in RBC deformability are due to membrane loss, but they are in agreement with the results of Nieuwland et al (29) in meningococcal sepsis, who found no difference in the glycophorin A plasma content in septic patients compared with healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…These rheological factors may include the size and shape of neonatal red blood cells, microclot formation in samples, contamination by interstitial fluid, hemolysis, altered protein quantity [17], protein deposition, fibrin aggregation, platelet or other cellular phenomena triggered by the test strip [10]. Interestingly, capillary samples were identified as a factor in the difference between LAB PCx and PG values but not between RN PCx and PG values.…”
Section: Discussionmentioning
confidence: 99%
“…These differences have been related to lower plasma proteins in neonates compared with adults [20,21,23,24]. Plasma viscosity is strongly dependent on total plasma protein concentration, but it is more influenced by macroproteins as fibrinogen than by smaller proteins as albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma viscosity is strongly dependent on total plasma protein concentration, but it is more influenced by macroproteins as fibrinogen than by smaller proteins as albumin. Aggregation of RBCs is entirely dependent on the concentration of macroproteins forming bridges among adjacent RBC [21,24]. Thus, the steady increase of macroproteins with gestational and postnatal age explains the concomitant rise in RBC aggregation.…”
Section: Discussionmentioning
confidence: 99%